2005
DOI: 10.1080/13600810500137889
|View full text |Cite
|
Sign up to set email alerts
|

Policy Reform, Economic Growth and the Digital Divide

Abstract: Rapid growth of internet use in high-income economies has raised the spectre of a “digital divide” that will marginalize developing countries because they can neither afford internet access nor use it effectively when it is available. Using a new cross-country data set, this paper investigates two proximate determinants of the digital divide: internet intensity (internet subscriptions per telephone mainline); and access to telecom services. Surprisingly, no gap in internet intensity was found. When differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
5
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 5 publications
6
101
5
2
Order By: Relevance
“…The above analysis draws attention to income as being the main common factor among the countries in the 'low-low' category. This finding is very much in line with crosscountry evidence on the role of income in explaining the variation in penetration rates of the Internet and mobile phones (Dewan et al 2004;Dasgupta et al 2002). From the point of view of penetration rates, one might then expect the countries in the opposite 'goodgood' category to have sharply higher income levels.…”
Section: The Country Classificationsupporting
confidence: 80%
See 1 more Smart Citation
“…The above analysis draws attention to income as being the main common factor among the countries in the 'low-low' category. This finding is very much in line with crosscountry evidence on the role of income in explaining the variation in penetration rates of the Internet and mobile phones (Dewan et al 2004;Dasgupta et al 2002). From the point of view of penetration rates, one might then expect the countries in the opposite 'goodgood' category to have sharply higher income levels.…”
Section: The Country Classificationsupporting
confidence: 80%
“…Econometrically this was already clear in 2002 from the study by Dasgupta et al which found that variations in penetration rates across countries had much to do with policy reform (and in particular with the liberalization of telecoms markets), as well as with variations in incomes 'Income remains a prime determinant of the digital divide, but our results suggest that appropriate economic and competition policies can sharply narrow the gap' (Dasgupta et al 2002).…”
Section: The 'Low-low' Categorysupporting
confidence: 48%
“…Each of these may serve as a gauge of the gap. Among these mono-or single topics, the literature mentions the following: income (Ebo, 1998), occupation (Losh, 2004;McLaren & Zappalà, 2002), gender and age (DiMaggio et al, 2004), education (Cornfield & Rainie, 2003), geographic centrality (Chen et al, 2003;Cornfield et al, 2003), ethnicity and race (Hoffman et al, 1999;2000;Novak et al, 1997), religiosity (Bell et al, 2004), language (Foulger, 2001), family structure (Kennedy et al, 2003), physical capacity (Le Blanc, 2000;Lenhart et al, 2003), frequency (Fox, 2004), time online (Spooner & Rainie, 2001), purpose (Center for the Digital Future, 2004), skills (Robinson et al, 2003), autonomy (Dasgupta et al, 2002), affordability (OECD/DSTI, 2001), competitive market structure (Dutta & Jain, 2004), ownership and density of computers and web sites (Sicherl, 2003), and communication infrastructure (Horrigan & Rainie, 2004;Horrigan, 2004aHorrigan, , 2004bKatz et al, 2003;Wareham et al, 2004).…”
Section: Calling For a Policy Frameworkmentioning
confidence: 99%
“…Measuring potential users is problematic since it requires access to micro data, which is unavailable for most of the countries in our sample. However, as noted by Dasgupta et al (2001), in the case of Internet, human capital requirements to use its basic applications (electronic mail and information search) are relatively low. Therefore, it seems reasonable to assume, as we do, that the entire population is a potential user.…”
Section: The Datamentioning
confidence: 99%